Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Kemampuan Representasi Matematis Bilangan Pecahan Siswa Kelas IV SD - Naila Kurnia Restu; Khotib Fathoni; Dian Indihadi (Jurnal Elementaria Edukasia, 2023)
This research was intended to describe a implementation of differentiated learning, Analysing student's mathematical repetent abilities, as well as analyzing the objective of fractional material learning classes by applying differentialized learning. Mathematical representation capabilities are essential applied to iv sd students, because to find the student's way of thinking of conveying mathematical ideas from abstract to concrete.Through learning differentiated students can learn based on their learning readiness rate so that students can follow learning easily and effectively.This research uses a method of study of class action (ptk ).The application of learning is different from the results of observation revealed that students can learn more actively by the way teachers give a learning experience based on students' readiness and using concrete media.Students' mathematical representation skills are increasing.